Application of Bioreactors to Improve Functionality of Bone Tissue Engineering Constructs: A Systematic Review - Nokhbatolfoghahaei, Hanieh; Rad, Maryam R.; Khani, Mohammad-Mehdi; Shahriari`, Shayan; Nadjmi, Nasser; Khojasteh, Arash (Current Stem Cell Research & Therapy, 2017)
Background: Traditional attempts to grow bone grafts in vitro have been based on culturing cell-scaffold constructs under static culture conditions. However, limitations associated with this approach have led to the development of various types of technologies and equipments. One of these is a bioreactor acting as an intermediate between static (in vitro) and dynamic (in vivo) conditions, which can mimic physiological and mechanical body conditions. Objective: The aim of this study was to systematically review the available literature on application of different types of bioreactors in bone tissue engineering. Methods: A thorough search in PubMed and Google Scholar databases from January 2011 to December 2016 was performed. All in vitro and in vivo studies about bioreactor applications in bone tissue engineering were included and categorized according to bioreactor types. Conclusion: A comprehensive systematic review of all the studies from the past five years yielded several findings: (1) combined bioreactors seem effective in bone tissue engineering; (2) 1- 2 ml/min is an appropriate flow rate range; (3) a cylinder is an appropriative scaffold shape; and (4) incubation of the scaffold with cells prior to transfer to the bioreactor followed by administration of osteogenic medium in the bioreactor seems an efficient approach to help cells properly attach and differentiate.
Keywords: perfusion bioreactor